1988
DOI: 10.1002/j.1460-2075.1988.tb03244.x
|View full text |Cite
|
Sign up to set email alerts
|

A light-entrained circadian clock controls transcription of several plant genes.

Abstract: Diurnal oscillations in steady‐state mRNA levels and transcription rates were measured for seven transcripts (five of which encode chloroplast‐localized proteins) in tomato seedlings: photosystem I and photosystem II chlorophyll a/b binding proteins (CAB/I and CAB/II), small subunit of RuBisCO (RBCS), actin, subunit II of the photosystem I reaction center (PSAD), subunit I of the photosystem II oxygen‐evolving enzyme (OEE1), and a biotin‐binding protein of unknown function. CAB/II mRNA levels were found to osc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
113
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(122 citation statements)
references
References 19 publications
9
113
0
Order By: Relevance
“…Patterns 3 and 4, characterized by an increase at the beginning of the day and a decrease in the second part of the day, are similar to those found for the small subunit of ribulose 1,5-bisphosphate carboxylase in pea (13), for light-harvesting complex protein in tobacco (25), for cab in tomato (9,18), and for cab9 1 R in Petunia (28). All of these previously described rhythms are circadian.…”
Section: Diumal Rhythmicity In Spot Intensitysupporting
confidence: 70%
See 1 more Smart Citation
“…Patterns 3 and 4, characterized by an increase at the beginning of the day and a decrease in the second part of the day, are similar to those found for the small subunit of ribulose 1,5-bisphosphate carboxylase in pea (13), for light-harvesting complex protein in tobacco (25), for cab in tomato (9,18), and for cab9 1 R in Petunia (28). All of these previously described rhythms are circadian.…”
Section: Diumal Rhythmicity In Spot Intensitysupporting
confidence: 70%
“…On the other hand, several recent studies have demonstrated diurnal or circadian rhythmicity in the level of specific mRNAs (8,9,13,18,21,25,28 (6). Gels were prepared for fluorography using Amplify (Amersham, UK) and exposed to preflashed Kodak X-Omat AR film, 48 Leaves of S. alba were harvested and their mRNA analyzed at the beginning (0 h), middle (4 h), and end of the day (8 h) as well as three times during the following night (12,16, and 20 h).…”
Section: Plant Materialsmentioning
confidence: 99%
“…In the unicellular dinoflagellate, Gonyaulax polyedra, the circadian rhythm in whole chain electron transport is related to the rhythm in PSII electron transport ( 18). Neither in higher plants ( 15) nor in algae (4) has a rhythm in Rubisco activity (or in any other aspect of the dark reactions) been substantiated, despite the fact that transcription and mRNA levels of the gene for the small subunit of Rubisco appear to be under circadian control (9,20).…”
Section: Introductionmentioning
confidence: 99%
“…In the unicellular dinoflagellate, Gonyaulax polyedra, the circadian rhythm in whole chain electron transport is related to the rhythm in PSII electron transport ( 18). Neither in higher plants ( 15) nor in algae (4) has a rhythm in Rubisco activity (or in any other aspect of the dark reactions) been substantiated, despite the fact that transcription and mRNA levels of the gene for the small subunit of Rubisco appear to be under circadian control (9,20).Recent work with P. vulgaris, in which circadian rhythms in conductance and photosynthesis were in phase and of similar period duration (-24.5 h), demonstrated that the intrinsic rate of photosynthesis, independent of stomatal effects, is under circadian control (10). Using this species, we examined several key enzyme activities and metabolite levels of the Calvin cycle to determine whether any were correlated with the endogenous rhythm in photosynthesis in extended periods of constant light.…”
mentioning
confidence: 99%
“…After the discovery of circadian regulation of mRNA levels (19), evidence accumulated suggesting that transcription of light-regulated genes is primarily under the control of the circadian clock (14) and that signal perception occurs via phytochrome (27). Moreover, the phase of the endogeneous clock can be shifted via phytochrome (27).…”
mentioning
confidence: 99%